S-Adenosylmethionine Inhibits Plasminogen-Activating Inhibitor-1 and Protects Male Mice from FOLFOX-Induced Liver InjurySummary - Alexandra Gangi; Tony W.H. Li; Youngyi Lim; Swati Chandla; Andrea Floris; Arash Khangholi; Maria Lauda Tomasi; Shelly C. Lu (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: FOLFOX, often used in patients with colorectal liver metastases, can cause sinusoidal obstruction syndrome (SOS) hindering subsequent treatment. S-adenosylmethionine (SAMe) is hepatoprotective and here we investigated whether it protects against FOLFOX-induced hepatotoxicity and defined the underlying mechanisms. Methods: A murine model of FOLFOX-induced SOS examined the effect of SAMe and plasminogen-activating inhibitor-1 (PAI-1). In vitro studies included primary mouse and human hepatocytes, Kupffer cells, hepatic stellate cells, and liver sinusoidal endothelial cells. Results: SAMe cotreatment completely blocked the induction of markers increased in FOLFOX-induced SOS and protected against liver injury. The most up-regulated gene was Serpine1, which encodes for PAI-1. SAMe blocked FOLFOX-induced expression and activation of nuclear factor (NF)-κB, which is known to activate SERPINE1/Serpine1 promoters. Interestingly, FOLFOX failed to activate hepatic NF-κB or cause liver injury in Serpine1 knockout male mice. Treatment of mouse hepatocytes with recombinant PAI-1 induced NF-κB activation; conditioned media from recombinant PAI-1 or interleukin-1β-treated hepatocytes, but not exosomes, increased the expression of proinflammatory cytokines and Cd31 in Kupffer cells and liver sinusoidal endothelial cells, respectively, which were blocked by SAMe. FOLFOX and interleukin-1β induced interaction between PAI-1 with urokinase plasminogen activator receptor in mouse liver and hepatocytes, respectively, which was blocked by SAMe. Recombinant PAI-1 requires interaction with uPA for full activation of NF-κB in hepatocytes. Neutralizing antibody against PAI-1 blocked interleukin-1β-mediated p65/PAI-1 activation in hepatocytes. Conclusions: FOLFOX treatment increased hepatocyte PAI-1 expression and liver injury, which were not observed in germline PAI-1 deficiency. Hepatocytes secrete PAI-1 to exert autocrine and paracrine effects to activate Kupffer cells and liver sinusoidal endothelial cells. SAMe protects against FOLFOX-mediated liver injury in part by inhibiting NF-κB activation and PAI-1 induction.